Formononetin Inhibits Migration and Invasion of MDA-MB-231 and 4T1 Breast Cancer Cells by Suppressing MMP-2 and MMP-9 Through PI3K/AKT Signaling Pathways - Zhou, R.; Xu, L.; Ye, M.; Liao, M.; Du, H.; Chen, H. (Hormone and Metabolic Research, 2014)
Formononetin is a naturally existing isoflavone, which can be found in the roots of Astragalus membranaceus, Trifolium pratense, Glycyrrhiza glabra, and Pueraria lobata. It was found to be associated with inhibition of cell proliferation and cell cycle progression, as well as induction of apoptosis in various cancer cell lines. However, the effect of formononetin on breast cancer cell metastasis remains unclear. In this study, we examined the effect of formononetin on the migration and invasion of breast cancer cells MDA-MB-231 and 4T1 in vitro and in vivo. Our data demonstrated that formononetin did not effectively inhibit the cell viability of MDA-MB-231 and 4T1 in 24 h with the concentration lower than 160 μmol/l. When treated with nontoxic concentration of formononetin, the migration and invasion of MDA-MB-231 and 4T1 cells were markedly suppressed by wound healing assay, chamber invasion assay, and in vivo mouse metastasis model. In vitro, formononetin reduced the expression of matrix metalloproteinase-2 (MMP-2), MMP-9 and increased the expression of tissue inhibitor of metalloproteinase-1 (TIMP-1) and TIMP-2. Furthermore, the immunoﬂuorescence and immunoblotting assays indicated that formononetin was very effective in suppressing the phosphorylation of Akt and PI3K. Collectively, these results suggest that formononetin inhibited breast cancer cell migration and invasion by reducing the expression of MMP-2 and MMP-9 through the PI3K/AKT signaling pathway. These findings demonstrate a potentially new therapeutic strategy of formononetin as anti-invasive agent for breast cancer.
Keywords: formononetin; breast cancer; migration; PI3K/AKT; matrix metalloproteinases